Hubungan Pengetahuan dan Sikap Mahasiswa Terhadap Penggunaan Stirofoam Sebagai Kemasan Makanan: Implikasi bagi Keberlanjutan Agribisnis: The Relationship Between Students' Knowledge and Attitudes Toward the Use of Styrofoam as Food Packaging: Implications for Agribusiness Sustainability - Annisa, Yulia; Nilda, Cut; Jannah, Hafizah (Universitas Medan Area, 2025)
The use of Styrofoam as food packaging has raised major concerns due to its negative impacts on health and the environment. This study aims to analyse the relationship between students' knowledge and attitudes toward Styrofoam usage as food packaging at Syiah Kuala University. Data were collected from 396 students through a survey employing probability sampling with a systematic random sampling method. A structured questionnaire was used to measure knowledge, attitudes, and purchase decisions. The findings reveal that students have a high level of knowledge regarding the risks of Styrofoam (average score: 4.04), yet maintain a neutral attitude toward its usage (average score: 2.55). Purchase decisions are primarily influenced by packaging availability in the market (average score: 3.06). Regression analysis indicates that knowledge and attitudes collectively explain 31.8% of the variance in purchase decisions. These findings highlight the need for enhanced consumer education and the promotion of sustainable packaging alternatives to support agribusiness sustainability.